INFLUENCE OF THE LASER CLADDING PARAMETERS AND SOLAR HEAT TREATMENT ON THE PROPERTIES OF BIOCOMPATIBLE INCONEL 718 COATINGS - Pascu, Alexandru; Stanciu, Elena Manuela; Roata, Ionut Claudiu; Hulka, Iosif; Uțu, Dragoș; Maior, Ioana (My University, 2017)
The paper presents the influence of the deposition process parameters in order to obtain dense and no major defect biocompatible alloys based on Inconel 718 hard coatings deposited on AISI 5140 carbon steel substrate using laser cladding method. Moreover, the cladded coating properties under optimal manufacturing conditions in terms of microhardness and tribological behaviour were improved by surface solar energy irradiation. The microstructure of the Inconel 718 coating before and after solar heat treatment was investigated by scanning electron microscopy (SEM) and the sliding wear resistance was determined by pin-on-disk method (POD).
Keywords: biocompatible coatings; laser cladding; solar heat treatment; wear resistance